Long-Lasting Suppression of Mechanical Allodynia in Mice by Intrathecal Administration of an Anti-Cell Adhesion Molecule 1 Antibody - Takasaki, Ichiro; Takeuchi, Fuka; Miyamae, Ryohei; Mochizuki, Yuto; Kinoshita, Hayate; Hagiyama, Man; Yoneshige, Azusa; Inoue, Takao; Narumi, Tetsuo; Ito, Akihiko (Medical principles and practice, 2025)
Objective: Cell adhesion molecule 1 (CADM1), an immunoglobulin superfamily member, is abundantly expressed on nerve fibers. Recently, the anti-CADM1 ectodomain antibody 3E1 has been shown to be potentially useful as a local anesthetic due to its high affinity for subcutaneous nerve fibers. When injected intrathecally into mice, where 3E1 accumulates, and whether it serves as an analgesic was examined. Methods: The 3E1 injection was detected using indocyanine green-based imaging and immunohistochemistry. As a neuropathic pain model, mechanical allodynia-affected mice were created by spinal nerve ligation (SNL). These mice were administered intrathecally with 3E1, control antibody, or pregabalin, and then the pain threshold of the hind paw was measured using von Frey monofilaments. After SNL, followed by intrathecal injection of 3E1, real-time PCR was conducted to examine the expression of pain-related genes, interleukin (IL)-1β, IL-2, IL-6, IL-10, tumor necrosis factor-α, chemokine (C-C motif) ligand (CCL) 2, CCL7, and CCL11. Results: Intrathecally, injected 3E1 was localized mainly on the dorsal root ganglion cell bodies and spinal dorsal horn nerve fibers, with no motor side effects. In the von Frey test, 3E1-injected mice exhibited higher pain thresholds for up to 2 weeks compared to control mice. Pregabalin also raised the threshold, but the effect dissipated within 1 day. While SNL increased mRNA expression of all pain-related genes examined in spinal dorsal horn neurons, 3E1 injection suppressed the increased expression of IL-6. Conclusion: 3E1 was suggested to be a potential ganglion-blocking analgesic and spinal anesthetic that acts ten or more times longer than pregabalin.